1997
DOI: 10.1097/00000478-199708000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Vascular endothelial growth factor (VEGF), a potent angiogenic and vascular permeability factor, is important in the angiogenesis of glioblastoma. A major difference between pilocytic astrocytoma, a grade I tumor, and the grade II fibrillary astrocytoma is the vascular proliferation, highly vascularized stroma, and great propensity for cyst formation in the former. In order to explore factors regulating such angiogenesis and cyst formation in pilocytic astrocytoma, we examined expression of VEGF and its recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, this putative mechanism requires the co-expression of c-met together with VEGFR-2 on glioma cells in vivo. Whereas VEGFR-2 can be readily detected in glioma cell lines in vitro, most studies suggest that in both murine and human glioma specimens in vivo expression of VEGFR-2 is mainly confined to vascular endothelial cells [51, 52, 77, 87, 112–114, 136], and potentially to a subset of cancer stem-like cells [49]. As such, it remains currently unclear whether the mechanism of bevacizumab-induced migration of glioma cells as proposed by Lu et al is of relevance in human glioblastoma in vivo.…”
Section: Angiogenic Signaling Pathways In Glioblastomamentioning
confidence: 99%
“…However, this putative mechanism requires the co-expression of c-met together with VEGFR-2 on glioma cells in vivo. Whereas VEGFR-2 can be readily detected in glioma cell lines in vitro, most studies suggest that in both murine and human glioma specimens in vivo expression of VEGFR-2 is mainly confined to vascular endothelial cells [51, 52, 77, 87, 112–114, 136], and potentially to a subset of cancer stem-like cells [49]. As such, it remains currently unclear whether the mechanism of bevacizumab-induced migration of glioma cells as proposed by Lu et al is of relevance in human glioblastoma in vivo.…”
Section: Angiogenic Signaling Pathways In Glioblastomamentioning
confidence: 99%
“…MCP-1 is reported to be upregulated in GBM and anaplastic astrocytoma and mediates the recruitment of macrophages with proangiogenic functions into tumor area in the gliomas (Leung et al, 1997;Lee et al, 2005). Dwyer et al demonstrated that IL-8 has the ability to function as an angiogenic factor in glioblastoma (Dwyer et al, 2012).…”
Section: Expression Of Chemokines and Chemokine Receptors In Brain Tumentioning
confidence: 99%
“…A dynamic relationship forms between the pre-neoplastic/ neoplastic and non-neoplastic stromal cell populations through stromagen and gliomagens release, which together facilitate tumorigenesis, tumor maintenance and glioma progression. endothelial growth factor (Forstreuter et al, 2002;Kerber et al, 2008), hepatocyte growth factor (Badie et al, 1999;Kunkel et al, 2001), monocyte chemoattractant protein-1 (Martinet et al, 1992;Leung et al, 1997) and the chemokine CX3CL1 (fractalkine) through activation of the CX3CR1 receptor (Held-Feindt et al, 2010). Monocyte chemoattractant protein-1 can also increase the surface expression of CX3CR1 on microglia (Green et al, 2006), thus providing amplification circuits for further microglia recruitment.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%